2020
DOI: 10.3390/su12020725
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants of Emerging Concern Removal in an Effluent of Wastewater Treatment Plant under Biological and Continuous Mode Ultrafiltration Treatment

Abstract: This work presents a case study of a wastewater treatment plant (WWTP), located in Biscay (Spain), in which the removal of high-occurrence contaminants of emerging concern (CEC) was studied. The existing biological treatment in the WWTP was complemented with a continuous ultrafiltration (c-UF) pilot plant, as a tertiary treatment. Thus, the effect on CEC removal of both treatments could be analyzed globally and after each operation. A total of 39 CEC were monitored, including pharmaceutical products, industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…From the 80:20 (defeathering:cooling) ratio, an average concentration of 1.82 mg/dm 3 was achieved, which is still 3.64 times higher than the recommended guideline according to the Kazakhstan drinking water quality standards. In this study, the membrane filtration treatment process was the main unit that can be associated with difficulty in the removal of ammonium; similar challenges of ammonium removal using membrane filtration processes have been observed in some other studies [52]. Although there is no evidence that ammonia is carcinogenic, ammonia has a toxic effect on healthy humans only if the intake becomes higher than the capacity to detoxify [53].…”
Section: Nitrate Nitrite Total Phosphorous and Ammoniummentioning
confidence: 75%
“…From the 80:20 (defeathering:cooling) ratio, an average concentration of 1.82 mg/dm 3 was achieved, which is still 3.64 times higher than the recommended guideline according to the Kazakhstan drinking water quality standards. In this study, the membrane filtration treatment process was the main unit that can be associated with difficulty in the removal of ammonium; similar challenges of ammonium removal using membrane filtration processes have been observed in some other studies [52]. Although there is no evidence that ammonia is carcinogenic, ammonia has a toxic effect on healthy humans only if the intake becomes higher than the capacity to detoxify [53].…”
Section: Nitrate Nitrite Total Phosphorous and Ammoniummentioning
confidence: 75%
“…Although UF technology is highly efficient at removing SS and pathogenic microorganisms, it is important to demonstrate that it is also effective in removing other compounds that could not be detected, either due to their low frequency of appearance or the low concentrations presented, below the limits of detection of the analytical techniques [9]. According to Table 5, it was observed that, in both systems, the toxicity decreased sharply until reaching a value less than 1.…”
Section: Effect Of the Self-cleaning System On The Water Qualitymentioning
confidence: 99%
“…The difference in performance is due to the changing adsorption capacity of the filter membrane according to the CEC. Ferreiro et al [9] studied the adsorption mechanism that occurred in an ultrafiltration process at certain concentrations of CECs, such as amitriptyline or sulfamethoxazole. According to the adsorption equilibria of such compounds [9], the high concentration of both CECs at the c-UF inlet favours retention during filtration.…”
Section: Removal Yields Of Cecs In the C-uf Pilot Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most of the treated potable-water resources may be polluted through deep-well injection of the effluent and surface outflow [ 27 ]. This flaw provides evidence that even drinking water is not free from these recalcitrant contaminants, since some compounds of EDCs, specifically plasticizers and steroidal hormones, were detected in drinking water, surface water, and groundwater (see Table 1) [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%